Development record and the effectiveness of foreign aid - Crosswell, Michael J. (USAID ArlingtonUS, 1998)
Examines the extent of progress (and lack of progress) in development. Posits that development performance on the whole has been postive, with much more success that failure, and much more progress than stagnation or decline. Suggests that prospects for future success are good.